A PATIENT’S TRUST IN THEIR DOCTOR ON THE FRAMEWORK OF MILLER’S FOUR SENSES OF AUTONOMY - ROTARU, Tudor-Ștefan; OPREA, Liviu (Studia Universitatis Babeş-Bolyai Bioethica, 2015)
A Patient’s Trust in Their Doctor on the Framework of Miller’s Four Senses of Autonomy. Both trust in the doctor-patient relationship and respect for patient autonomy are basic principles for an ethical medical practice. Trust is particularly important in filling in the gap between scientific evidence and clinical practice. This is so because patient trust is associated with patient compliance with therapeutic recommendations. This paper argues that although central to modern medical care, autonomy cannot always be preserved in situations dealing with trust. People trust or distrust without being necessarily autonomous. This happens even if no moral rule is violated by either the doctor or patient. Încrederea pacientului în medic din perspectiva celor patru sensuri ale autonomiei (Miller, 1981). Atât încrederea cât și autonomia sunt principii de bază pentru o practică medicală etică. Încrederea este îndeosebi importantă în depășirea distanței dintre dovezi științifice și practică. Articolul de față argumentează faptul că, deși centrală îngrijirii medicale moderne, autonomia nu poate fi păstrată întotdeauna în situații care presupun încredere. Oamenii au sau nu au încredere fără ca ei să fie în mod necesar autonomi. Acest fapt are loc chiar și în situația în care nicio regulă morală nu este violată de medic sau pacient. Cuvinte-cheie: încredere, autonomie, etică medicală